Factors predicting sleep quality among university students in Iceland - Jökull Starri Hagalín 1995- (2021)
Studies have indicated that the poor quality of sleep among university students can result in physical and psychological health problems. The COVID-19 pandemic has uprooted communities and daily life worldwide, university students being no exception. This study aims to examine Icelandic university student’s sleeping quality and its relationship with various factors. Particularly its relation to depressive, stress, and anxiety levels. Demographic variables such as gender, age, and education level were also examined. This study consisted of a sample of 731 students, 433 females (59,2 %) and 297 males (40,6%). The Pittsburgh Sleep Quality Index was used to measure the student’s sleep quality over the past month. Patient Health Questionnaire (PHQ-9) was used for the purpose of screening for depressive symptoms. The Perceived Stress Scale (PSS-10) was utilized for assessing the stress levels of the students. The General Anxiety Scale (GAD-7) was used for assessing the anxiety levels of students. Hypothesis 1 was supported, if students scored high on the PSQI scale they were likely to score high on the PHQ-9 scale as well. Hypothesis 2 was not supported as there was not a significant statistical between genders regarding sleep quality. Hypothesis 3 was not supported, as there was no significant statistical difference regarding the age of the students and their outcome on the PSQI scale. Hypothesis 4 was partially supported; the most common answer was that the COVID-19 pandemic had a negative effect on their mental health. Hypothesis 5 was partially supported, 56.7% of students had mild to severe anxiety symptoms. Keywords: sleep quality, depressive symptoms, stress, anxiety, university, COVID-19 Rannsóknir hafa sýnt fram á að skortur á svefni og lélegur nætursvefn háskólanema getur leitt til ýmsa alvarlegra líkamlega og sálræna heilsufars vandamála. COVID-19 heimsfaraldurinn hefur haft áhrif á samfélög og daglegt líf um alla veröld og þar eru háskólanemar engin undantekning. Þessi rannsókn miðaðist að því að kanna ...